O Brasil e o regime Internacional de Não-Proliferação de Armas Nucleares: adesão resistida na inserção brasileira - Souza, Leandro Bessa [UNESP] (2013)
The objective of the present work is to analyze Brazil's adhesion process into the Nuclear Weapons Non-Proliferation Regime since the end of the military regime in the country in 1985, to identify continuity elements in the Brazilian Foreign Policy on this issue until the end of Lula's second mandate. We try to study the hypothesis that, in spite of changes of political parties and presidents on the country's command, Brazil adopted a strategy of progressive critical and active participation in the discussions of the future of the regime in different international forums. Its policy followed two basic master lines: the defense of the global nuclear disarmament and the country's right to develop nuclear technology for pacific ends. We founded our study in the analysis of the formation and contradictions of said regime, as well on the advances and recoils of Brazil's nuclear activities. We conclude that during the examined time lapse, the country's foreign policy had as permanency element what we called resisted adhesion, consistent with conducting the regime's evolution to guarantee autonomy spaces for Brazil's action in the nuclear area, avoiding assume bigger obligations for the country, in particular the ones related to nonproliferation, even if in times only by symbolic actions. This directive was maintained during Lula's government and was intensified during his second mandate, which coincides with the country's apparent interest in strengthening its nuclear projects on its different aspects. Despite of it, we don't find possible to affirm that there is a consonance between the Brazilian investments on the nuclear area (which oscillate during the studied period) and its position on the regime in exam.